Changes in speed and efficiency in the front crawl swimming technique at 100m track - Stastny, J.; Motycka, J.; Batorova, M.; Pasek, . (Journal of Human Sport & Exercise, 2016)
The aim of our research is to show how the speed of competitive swimmers at a 100m track (4 x 25m) develops and to find out if there are any considerable changes in swimming efficiency. As for the speed, we expect its gradual decrease caused by fatigue. Efficiency of swimming is directly determined by mastering of swimming techniques. However the question is whether it is also influenced by fatigue. It expands our earlier publications and includes measurements conducted not only at the 50m swimming track (two sections /25m legs) but also those taken at the 100m track (four sections/25m legs). Thanks to our measuring device called Tachograph, we have been able to record and subsequently analyse the results of 10 male and seven female swimmers, all being between the ages of 18 and 23 / 26. Research shows that the average mean speed in male categories declines from 1.65 m/s reached in the first section down to1.50m/s in the fourth section. The decrease seems to be linear during the first three sections while it is not so significant in the fourth swimming legs. Efficiency of swimming slightly decreases from 0.949 to 0.936. As for the female swimmers, their average mean speed decreases from 1.46m*s -1(measured in the first section) to1.34m/s in the fourth section. The decline is more or less linear, with a slight reduction in value. Efficiency has a subtle declining tendency (from 0.967to0.961). In both male and female categories, the speed of swimming slightly declines, whereas changes in the efficiency of swimming are not substantial.